Branding and contemporary cognition : a semiotic approach to communication effectiveness - Dias, Patrícia (2014)
This paper explores the role of cognitive structures and socially shared meanings in communication effectiveness, focusing concretely on brand communication. Traditionally in communication sciences, ambiguity and polysemy have been considered prejudicial to the effectiveness of communication. However, we argue that in branding, the more possible meanings a brand alludes to, the more people are able to identify with it and emotionally connect to it, thus contributing to the effective communication of the brand, understood as the building or reinforcement of a positive relationship between the receiver and the brand. Our main argument is explored within a theoretical framework that is founded on the following assumptions: a) the new media are one of the main factors that shape the contemporary society; b) this shaping takes place on a cognitive level, thus originating concrete cognitive structures that are characteristic of the contemporary society; c) brands are more effective if they allude to meanings shared on a social and cultural level and if they are adjusted to contemporary cognition. We empirically test our arguments by exploring 15 cases of rebranding of Portuguese enterprises. We focused on the logotype as the main element of the brand, and we conducted a comparative visual analysis which combined the methods of content analysis and semiotic analysis. Plus, we complemented our visual analysis with qualitative interviews to one member of each organization who was involved in the rebranding process. Our findings showed that the brands which allude to more meanings and to more ambiguous meanings and which have more levels of meaning (denotation, connotation, myth) are more effective in generating identification and emotional relationships. Furthermore, they are cognitively more engaging and involving. We hope that our research contributes in an applied way to enhance creativity and communication effectiveness in brand design and in branding.